(untitled) (World Bulletin of Public Health, 2025)
Autoimmune hepatitis predominantly occurs in women and often manifests at a young age. It has been proven that patients diagnosed at later stages have a higher risk of developing liver cirrhosis. Therefore, early diagnosis significantly increases treatment effectiveness and improves the likelihood of long-term remission. Although immunosuppressive therapy is effective, long-term treatment is required to prevent disease recurrence. In some patients, intolerance or adverse effects of medications may occur, necessitating the development of individualized treatment strategies. Patients who are diagnosed late or are resistant to standard therapy may develop liver failure, in which case liver transplantation remains the only solution.